Análise de pedigree e estimativas de parâmetros genéticos para características reprodutivas em bovinos da raça Brahman - Cavani, Ligia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The genetic diversity in Brahman cattle in Brazil may decrease over the years and can be even lower for stabled animals, moreover, it is expected that the phenotypic variance of reproductive characteristics can be little explained by genetic variance. The aims of this study were to evaluate the behavior of genetic diversity over a period of 18 years and stabled animals by pedigree analysis and estimates genetic parameters for ge at first interval (IPP), calving interval (IEP), reconception (REC) and stayability (HABP) reproductive traits of Brahman cattle in Brazil, aiming to develop selection strategies for genetic progress of breed. The pedigree was analyzed in three ways: considering all the pedigree information (Pt); dividing the pedigree information in two periods from 1994 to 2004 (P1) and from 2005 to 2012 (P2), according inbreeding; and dividing the pedigree data according to breeding management of animals on pasture (Ppasto) and stabled (Pest). Coefficient inbreeding (F) values were 0,31%, 0,07%, 0,50%, 0,30% and 0,22% for Pt, P1, P2, Ppasto, Pest, respectively. Generation intervals (IG) values for Pt, P1, P2, Ppasto, Pest were 4,73, 3,35, 4,50, 4,65, 4,81 years, respectively. For the results of the parameters based on the probability of gene origin: number of founders (Nf), effective number of founders (f e ), effective number of ancestors (f a ) and founder genome equivalents (f g ), in all situations f e > f a > f g and there was a decrease in values of estimated parameters between periods (P1 e P2) and between breeding management (Ppasto e Pest). Values close to 1 observed for f e /f a and f g /f e show no genetic bottleneck and the process of genetic drift was small. For estimate the genetic parameters for reproductive traits, two-trait analyzes were used, using the linear animal model for IEP and IPP and the animal threshold model for REC and HABP. The mean heritability were ...

Em bovinos da raça Brahman criados no Brasil a diversidade genética pode diminuir ao longo dos anos e pode ser ainda menor para animais estabulados, além disso, espera-se que a variância fenotípica de características reprodutivas pode ser pouco explicada pela variância genética. Portanto, objetivou-se avaliar o comportamento da diversidade genética durante um período de 18 anos e de animais estabulados por meio da análise de pedigree e estimar os parâmetros genéticos para as características idade ao primeiro parto (IPP), intervalo entre partos (IEP), reconcepção (REC) e habilidade de permanência (HABP) em bovinos da raça Brahman, visando o desenvolvimento de estratégias de seleção para o progresso genético da raça. O pedigree foi analisado de três maneiras: considerando toda a informação de pedigree (Pt); dividindo as informações de pedigree em dois períodos de 1994 a 2004 (P1) e de 2005 a 2012 (P2), de acordo com nível médio endogâmico; e dividindo os dados de pedigree de acordo com a condição de criação dos animais, a pasto (Ppasto) e estabulado (Pest). Os valores dos coeficientes endogâmicos (F) foram de 0,31%, 0,07%, 0,50%, 0,30% e 0,22% para Pt, P1, P2, Ppasto, Pest, respectivamente. Os intervalos de geração (IG) para Pt, P1, P2, Ppasto, Pest foram de 4,73, 3,35, 4,50, 4,65, 4,81 anos, respectivamente. Para os resultados dos parâmetros com base na probabilidade de origem do gene: número de fundadores (Nf), número efetivo de fundadores (fe), número efetivo de ancestrais (fa) e número efetivo de genomas remanescentes (fg), fe > fa > fg em todas as situações e ocorreu uma diminuição nos valores dos parâmetros estimados entre períodos (P1 e P2) e entre condição de criação (Ppasto e Pest). As razões fe/fa e fg/fe foram próximas de 1, indicando que não houve gargalo genético e que o processo de deriva genética foi pequeno. Para estimar os parâmetros...
Keywords: Animais - Melhoramento genetico; Endogamia; Genbalogia; Genomas; Zebu; Inbreeding